Fluxes of nutrient uptake and leaf chlorophyll of chia (Salvia hispanica L.) under herbicides spray - Anuj Kumar; Moola Ram; J. P. Tetarwal; Vikash Meena; Devi Lal Kikraliya; Hitesh Genan; Anju Bijarnia (Annals of Agricultural Research, 2024)
A field experiment was conducted at research farm of Agricultural Research Station, Mandor, Agriculture University, Jodhpur during Rabi season of 2021-22 to find out efficacy of different herbicides on chia (Salvia hispanica L.) under western Rajasthan. It was found that application of bentazon 48% SL 750 g/ha recorded significantly higher nutrient content in seed and straw (1.410 & 0.746, 0.473 & 0.182, 0.318 & 0.926 % NPK, respectively) and nutrient uptake by seed and straw (6.97 & 1.47, 2.34 & 0.36, 1.57 & 1.83 kg/ha NPK, respectively) recorded maximum. It also recorded significantly higher seed yield (495 kg/ha), straw yield (197 kg/ ha), biomass yield (755 kg/ha) and harvest index (65.56). In cash of chlorophyll content in leaf was recorded maximum (46.44 @ 60DAS) with the application of bentazon 48% SL 750 g/ha.